2022
DOI: 10.21776/ub.biotropika.2022.010.02.07
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity Screening Of Bacterial Isolates Associated With Seaweed Eucheuma cottonii From Coastal Area In Buleleng, Bali

Abstract: Seaweeds like other marine organisms develop a strong association with prokaryotic communities, especially bacteria. Many of these associated bacteria play an important role in synthesizing secondary metabolites which are beneficial for their host, especially against predation or infection. In Indonesia, Eucheuma cottonii is one of the seaweed species that has been cultivated widely. However, only limited study has been reported on bacterial isolates and their antibacterial activity from E. cottonii. Bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Sejumlah penelitian melaporkan bahwa Aktinobakteria yang berasosiasi dengan rumput laut menunjukkan aktivitas antibakteri terhadap sejumlah bakteri patogen (Ulfah et al, 2018). Selain kelompok Aktinobakteria, aktivitas antibakteri dari isolat yang berasosiasi dengan rumput laut juga banyak dilaporkan dari jenis bakteri lain seperti Bacillus sp ., Purnami et al,2022.…”
Section: Pembahasanunclassified
“…Sejumlah penelitian melaporkan bahwa Aktinobakteria yang berasosiasi dengan rumput laut menunjukkan aktivitas antibakteri terhadap sejumlah bakteri patogen (Ulfah et al, 2018). Selain kelompok Aktinobakteria, aktivitas antibakteri dari isolat yang berasosiasi dengan rumput laut juga banyak dilaporkan dari jenis bakteri lain seperti Bacillus sp ., Purnami et al,2022.…”
Section: Pembahasanunclassified
“…This can have negative impacts on seaweed farming industry (Brakel et al 2021). Despite the presence of harmful bacteria, studies showed that bacteria associated with E. cottonii was a source of antibacterial substances, but investigations on this aspect were still limited (Purnami et al 2022). Several studies on the isolation and identification of bacteria in E. cottonii seaweed infected with ice-ice disease showed the presence of bacteria such as Vibrio sp., Pseudomonas sp., and Bacillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Seaweed-associated bacteria contribute in growth, morphogenesis, and protection by synthesizing various bioactive molecules including antibacterial compounds (Singh & Reddy, 2014). Unlike its host, studies on E. cottonii-associated bacteria are still limited (Hafsan et al, 2019;Purnami et al, 2022). A previous study reported isolation of Aeromonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…that inhibit S. aureus and E. coli. Furthemore, a recent study has reported 23 bacterial isolates from E. cottonii collected at the coastal waters of Buleleng, Bali with six of these isolate displayed antibacterial activity against S. aureus, S. mutans, E. coli, and K. pneumoniae (Purnami et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation